Social Security Guide : The White Paper and the Beveridge Report Compared - Great Britain. Office of the Minister of Reconstruction. Social insurance ; Great Britain. Inter-departmental Committee on Social Insurance and Allied Services. Social insurance and allied services ; Beveridge, William Henry Beveridge, Baron, 1879-1963; Clarke, Joan Simeon (London : The Social Security League)
1944-10-01 1944 1940s 20 pages at week-ends, nor is milk, although holiday milk schemes have been tried. No doubt the Government has this side of the problem in mind. So the real question outstanding is this: Can a child be properly maintained on 5/- plus five dinners and five glasses of milk weekly? This is a question for the experts. It is of vital importance to the family whose sole income is derived from benefit, and no doubt the Government has framed its plans for free school meals and milk on lines which provide a satisfactory answer. Two different lines of thinking seem to have crossed here; one is the argument that children's allowances should not provide full maintenance but should be a general grant to family funds, further helped by services in kind. The other quite unrelated argument is that when families are altogether dependent on benefit, the sums paid in respect of children shall be enough to keep those children fit. This argument has no reference whatever to the size of allowances, if any, which are paid for children in families living on income other than benefit. In this country, for example, there are at present no children's allowances paid universally, but Assistance Board rates, which are graded according to the age of the children, from 6/- to 9/- attempt to provide an adequate nutritional standard. Beveridge was able to use the same rate for all children, whether the parents were on benefit or not, because he had already based his universal children's allowances on the subsistence level. It is a neat idea to draw in the first child as soon as the parents begin to draw benefit, and to make no further cash allowance. But if the universal children's allowance is not sufficient for full maintenance, the idea loses its validity. The family income will not meet family needs. One way to get round this problem would be to draw in the first child when the family is on benefit, and additionally to add a few shillings to the parents' benefit for each dependent child, possibly grading these small sums according to the ages of the children. This would not be more complicated to administer than the present children's allowances paid with unemployment benefit, and it would avoid any interference with the steady routine of paying flat-rate universal children's allowances in the normal way. 6. OLD AGE — What is the proper way to treat the old? Instinct suggests high pensions, suitable housing, and the sort of amenities which will give old people a sense of friendly appreciation for the work they did in the past. Unfortunately, this is not so easy as it sounds. Our population is growing older. Every year there will be more old persons drawing pensions, and fewer workers to make the goods on which these pensions will be spent. The White Paper explains this clearly:— "Whereas in 1945 it is estimated that there will be 16 pensioners to every 100 contributors, there will by 1975 be about 31 pensioners to every 100 contributors." (Para. 82). Not only is the number of pensioners increasing, but there is a steady demand that the amount of the pensions shall also increase. We have to pay bigger pensions to more people. This means that an increasing amount of the goods which we produce will be used by the aged and, naturally, that less will be left for the producers and 10 15X/2/453/3